Peningkatan Kompetensi Guru dan Kualitas Penyusunan RPP Berbasis HOTS (Higher Order Thinking Skill) Melalui Supervisi Akademik Bagi Guru MTs Negeri I Gunungkidul - Ngadiyan Ngadiyan (Jurnal Pendidikan Madrasah, 2022)
This study aims to obtain data on the quality and quantity of teacher competencies in preparing learning implementation plans. This research is an action research carried out in two cycles including the stages of planning, implementation, observation and reflection. The research approach using academic supervision includes traditional supervision and clinical supervision which is carried out in groups based on the subject family. The subjects of the study were teachers in MTs Negeri I Gunungkidul. There are three findings of academic supervision of the subject cluster base group model scientifically can improve teacher competence in compiling the syllabus and rpp in MTs N 1 Gunungkidul, namely: 1) increasing the quality of the syllabus from 64% to 80%; 2) increased the number of RPP qualities from 66% to 89%; and 3) increased teacher competence in compiling the HOTS syllabus and RPP by 23% and 24%.